(untitled) (Indian Journal of Arid Horticulture, 2025)
Cordia myxa (Roxb.) is commonly known as "lasora". It is an under-exploited fruit and herbal tree in rural India. It belongs to the family Boraginaceae and probably originated in the Indian sub-continent (Samadia, 2005). It is widely distributed in the arid and semi-arid regions of India and yields fruit during April-May. Immature fruits of lasora are used for making pickles and vegetable curries, and matured fruits are very nutritious, rich in carbohydrates and total ash. This fruit tree is not a commercial crop but it grows naturally in the non-cultivable or waste lands, backyards, on roadsides and farm boundaries (Samadia, 2005). Conservation and understanding genetic diversity of this under-exploited crop is the primary requirement for identification of superior genotypes for its improvement and exploitation. Considerable diversity on the basis of morphological parameters has been reported in the naturally growing population of lasora in Rajasthan (Samadia, 2007).